Effects of microbial community and disease resistance against Vibrio splendidus of Yesso scallop (Patinopecten yessoensis) fed supplementary diets of tussah immunoreactive substances and antimicrobial peptides. Issue 121 (February 2022) - Mi, Rui; Li, Xuejun; Sun, Yongxin; Wang, Qingzhi; Tian, Bin; Ma, Shuhui; Meng, Nan; Li, Yajie; Wen, Zhixin; Li, Shuying; Wang, Xiaoyan; Du, Xingfan
Abstract: This study was conducted to investigate the effects of dietary supplementation of tussah immunoreactive substances (TIS) and antimicrobial peptides (AMPs) on microbial community and resistance against Vibrio splendidus of Yesso scallop Patinopecten yessoensis . Scallops were fed with the basal diets supplemented with TIS (T group), AMPs (A group), or both of the two (TA group). After the feeding trial, the microbial community changes were evaluated, and the challenge test with V. splendidus was conducted, as well as the immune parameters and digestive enzyme activities were determined. The results revealed that the TA group was more capable of modulating the bacterial community composition of scallops by increasing the potentially beneficial bacteria and suppressing the pathogenic microorganism during the feeding trial. After injection, the cumulative mortality rate in TA group was notably lower than others. In addition, the TA group showed better digestive and immune parameters involved in digestive capacity, phagocyte function, phosphatase-responsiveness, and oxidation resistance. These results collectively confirmed that dietary TIS and AMPs in diet could effectively modulate the microflora structure and improve disease resistance against V. splendidus of scallop, and the positive effects were more obvious when dietary supplementation of them in combination. Graphical abstract: Image 1 Highlights: It is the first time to explore the positive effects of TIS and AMPs on scallops. Dietary TIS and AMPs could optimize the microbial community of scallops. Dietary TIS and AMPs could improve the disease resistance of scallops. The positive effects were more obvious by applying TIS and AMPs in combination.